Economic Empowerment via Innovative Zakat Utilization: Lessons from a Multicultural Village in Ponorogo - Distyana Dwiyanti; Luhur Prasetiyo (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This study investigates the economic empowerment of mustaḥiq (zakat beneficiaries) through the Desa Berdaya Program in Mrican Village, Ponorogo, with a focus on sheep-based empowerment strategies. The research examines the forms of empowerment (breeding, fattening, and investment), the factors influencing its implementation, and its impact on beneficiaries' welfare. The program, implemented by Rumah Zakat, leverages zakat funds to promote self-reliance among beneficiaries and transform them into potential muzakki (zakat payers). Using qualitative methods, data were collected through interviews, observations, and documentation. The findings reveal that empowerment addresses socio-economic inequalities, such as low education levels, inconsistent income, and limited knowledge among beneficiaries. The program significantly improves economic, social, and spiritual welfare by enhancing income, fostering community collaboration, and strengthening religious values. Challenges identified include delays in resource provision and unclear profit-sharing mechanisms, highlighting the need for improved management practices. Overall, the study underscores the potential of productive zakat as a sustainable tool for poverty alleviation and community development.